Catalytic Alkylation of Depolymerized Neyveli Lignite - Krishnamurthy, N.; Arul Leo Bastin, J.; Palanichamy, M.; Chellamani, A.; Vallinayagam, P.; Madhavan, D. (Asian Journal of Chemistry, 2014)
Catalytic alkylation of depolymerized Neyveli lignite was carried out with various alcohols as alkylating agents in presence of phosphotungstic acid as a catalyst. Alkylation was evident from the higher extractability of alkylated depolymerized lignite in various solvents. Hence it is proved three dimensionally bonded alkyl chains for coal structure cleaving of which by alkylation permits additional depolymerization. The IR and NMR spectra also conformed the alkylation reaction. A suitable alkylation mechanism is proposed. Thermogravimetric analysis results revealed enhanced thermal stability for alkylated depolymerized products.